Solve:
(x+5)(x-3)=-2(2x+7)
Expand.
(x+5)(x-3)=-4x-14
FOIL.
x^2+2x-15=-4x-14
Add 4x to both sides.
x^2+6x-15=-14
Add 14 to both sides.
x^2+6x-1
x^2+6x-1 is a quadratic equation in standard form: ax^2+bx+c, where a=1, b=6, c=-1.
Use the quadratic formula to solve.
x=(-b+-sqrt(b^2-4ac))/(2a)
Substitute the given values into the formula.
x=(-6+-sqrt(6^2-4xx1xx-1))/(2xx1)
Simplify.
x=(-6+-sqrt(36+4))/2
x=(-6+-sqrt(40))/2
Prime decompose sqrt(40).
x=(-6+-sqrt(2xx2xx2xx5))/2
x=(-6+-sqrt(2^2xx2xx5))/2
x=(-6+-2sqrt10)/2
Simplify.
x=-3+-2sqrt10
Solutions for x.
x=color(red)(-3+2sqrt10),color(blue)(-3-2sqrt10